Relationship between horizontal condylar angle and radiographically detectable morphological changes of the condyle in asymptomatic and symptomatic patients with TMD - Wafa Alfaleh (Elsevier, 2021)
Background: The relationship between horizontal condylar angle (HCA) measurements and radiographically detectable morphological changes of the condyle in patients with temporomandibular disorder (TMD) is an area of controversy in dentistry. Aim: This study sought to determine the effect of the HCA on radiographically morphological changes in the condyles of asymptomatic and symptomatic patients with TMD. Material & methods: Cone beam computed tomography (CBCT) scans were used of patients with 146 temporomandibular joints (TMJ) with and without symptoms of TMD. The reconstructed axial plane was adjusted to depict the condyle in maximum width. The HCA was established and measured as the angle formed between the condylar long axis intersecting with the coronal plane. Each condyle long axial was determined independently from the other joint by two oral and maxillofacial radiologists. The average of the readings from the two examiners was used for statistical analysis. Results: Based on the clinical symptoms, the mean of the HCA in the symptomatic joint was 27.69°, which was slightly greater than the angle measured in asymptomatic patients of 25.6°; however, this was not a statistical difference. No significant differences existed in the mean of the HCA between the joint with and without radiographic arthritic findings in both groups. In both groups, none of the arthritic findings manifested in the affected joint that had influenced the HCA. Conclusion: The HCA was increased in the symptomatic group but had no direct influence on joint's morphological changes in the asymptomatic and symptomatic patients.